2021
DOI: 10.1038/s41598-021-86926-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of two intervention methods for stony coral tissue loss disease on Montastraea cavernosa

Abstract: Stony coral tissue loss disease (SCTLD) was first observed in Florida in 2014 and has since spread to multiple coral reefs across the wider Caribbean. The northern section of Florida’s Coral Reef has been heavily impacted by this outbreak, with some reefs experiencing as much as a 60% loss of living coral tissue area. We experimentally assessed the effectiveness of two intervention treatments on SCTLD-affected Montastraea cavernosa colonies in situ. Colonies were tagged and divided into three treatment groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 41 publications
1
80
0
Order By: Relevance
“…It has been documented in the field that topical antibiotic applications are effective in halting SCTLD lesion progression (Aeby et al, 2019;Neely et al, 2020; Measurements were taken at the halfway point between initial disease appearance and mortality, on average 3.5 days. Shilling et al, 2021); however, the effectiveness is likely to remain localized in the region of application (Neely et al, 2020), while new lesions can appear in other areas of the colony following treatment. Colony size may be a factor in lesion appearance among the different treatment distances.…”
Section: Lesions Developed On Donor Coral Fragments Isolated From Tissue Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been documented in the field that topical antibiotic applications are effective in halting SCTLD lesion progression (Aeby et al, 2019;Neely et al, 2020; Measurements were taken at the halfway point between initial disease appearance and mortality, on average 3.5 days. Shilling et al, 2021); however, the effectiveness is likely to remain localized in the region of application (Neely et al, 2020), while new lesions can appear in other areas of the colony following treatment. Colony size may be a factor in lesion appearance among the different treatment distances.…”
Section: Lesions Developed On Donor Coral Fragments Isolated From Tissue Lossmentioning
confidence: 99%
“…Like many coral diseases, definitive pathogen identification for SCTLD has been unsuccessful. Studies have indicated that lesion progression can be slowed down or halted on 1 https://floridadep.gov/sites/default/files/Copy%20of% 20StonyCoralTissueLossDisease_CaseDefinition%20final%2010022018.pdf some coral species with topical antibiotics (Aeby et al, 2019;Neely et al, 2020;Shilling et al, 2021), suggesting that the presumptive pathogen(s) for SCTLD may have a bacterial component. Additionally, some studies have identified differences in bacterial communities between apparently healthy and SCTLD-affected corals, but whether identified bacteria are primary pathogens or secondary opportunistic infections is unknown (Meyer et al, 2019;Rosales et al, 2020;Ushijima et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, because the infectious agents in WBD can be treated with antibiotics (Kline and Vollmer, 2011;Sweet et al, 2014) it has been suggested that several bacterial taxa are likely the potential pathogens. For SCTLD it has recently been shown that topical amoxicillin treatments successfully arrested disease lesion progression on multiple species of corals affected by the disease (Neely et al, 2020) giving credence to the hypothesis that the pathogen(s) responsible are also likely to be bacterial in origin (see also Miller et al, 2020;Neely et al, 2021b;Shilling et al, 2021;Walker et al, 2021). However, examination of tissues from SCTLD affected corals by transmission electron microscopy suggests that SCTLD may be a viral infection of zooxanthellae that leads to coral host cell death (Work, 2021: see also Correa et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Epidemiological models show that progression of SCTLD along the FRT was also consistent with waterborne transmission and was positively associated with high coral diversity (Muller et al, 2020). Application of antibiotics to affected coral colonies slows or stops disease progression both in the field (Neely et al, 2020;Shilling et al, 2021;Walker et al, 2021) and in the laboratory (Aeby et al, 2019) implicating the involvement of bacterial pathogens in the disease process.…”
Section: Introductionmentioning
confidence: 95%